Cancer of the esophagus and esophagogastric junction—Major changes in the American Joint Committee on Cancer eighth edition cancer staging manual. (26th May 2017) - Rice, Thomas W.; Gress, Donna M.; Patil, Deepa T.; Hofstetter, Wayne L.; Kelsen, David P.; Blackstone, Eugene H.
Abstract: Answer questions and earn CME/CNE New to the eighth edition of the American Joint Committee on Cancer (AJCC) Cancer Staging Manual for epithelial cancers of the esophagus and esophagogastric junction are separate, temporally related cancer classifications: 1) before treatment decision (clinical); 2) after esophagectomy alone (pathologic); and 3) after preresection therapy followed by esophagectomy (postneoadjuvant pathologic). The addition of clinical and postneoadjuvant pathologic stage groupings was driven by a lack of correspondence of survival, and thus prognosis, between both clinical and postneoadjuvant pathologic cancer categories (facts about the cancer) and pathologic categories. This was revealed by a machine‐learning analysis of 6‐continent data from the Worldwide Esophageal Cancer Collaboration, with consensus of the AJCC Upper GI Expert Panel. Survival is markedly affected by histopathologic cell type (squamous cell carcinoma and adenocarcinoma) in clinically and pathologically staged patients, requiring separate stage grouping for each cell type. However, postneoadjuvant pathologic stage groups are identical. For the future, more refined and granular data are needed. This requires: 1) more accurate clinical staging; 2) innovative solutions to pathologic staging challenges in endoscopically resected cancers; 3) integration of genomics into staging; and 4) precision cancer care with targeted therapy. It is the responsibility of the oncology team to accurately determine and record registry data, which requires eliminating both common errors and those related to incompleteness and inconsistency. Despite the new complexity of eighth edition staging of cancers of the esophagus and esophagogastric junction, these key concepts and new directions will facilitate precision cancer care.CA Cancer J Clin 2017;67:304–317. © 2017 American Cancer Society.